IMPLEMENTASI MODEL PEMBELAJARAN DEEP DIALOGUE CRITICAL THINKING PADA PEMBELAJARAN KARYA FIKSI KELAS VIII MTSN 3 LANGKAT - Bella Pratiwi, Eka; Yuhdi, Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to (1) Describe the implementation of the Deep Dialogue Critical Thinking (DDCT) learning model in learning fictional works of class VIII MTsN 3 Langkat. 2) Describe the learning motivation of students when following the learning process by teachers when using the Deep Dialogue Critical Thinking (DDCT) learning model. This study uses a qualitative approach with a case study method. The subjects of this study were Indonesian Language Teachers of class VIII MTsN 3 Langkat. The research instruments used were observation, interviews, behavioral observation and questionnaires. The results of the study (1) The implementation of the DDCT model went well and was able to create active, dialogical learning, and supported the development of critical thinking skills of students in understanding and writing fictional work review texts, (2) The learning motivation of students during learning using the Deep Dialogue Critical Thinking (DDCT) model in class VIII MTsN 3 Langkat showed a positive tendency in all aspects of learning motivation. It is hoped that the results of this study will be useful for educators, students, and further research who want to implement learning models to encourage student learning motivation.